2013
DOI: 10.1038/srep01340
|View full text |Cite
|
Sign up to set email alerts
|

Impact of simulated microgravity on the normal developmental time line of an animal-bacteria symbiosis

Abstract: The microgravity environment during space flight imposes numerous adverse effects on animal and microbial physiology. It is unclear, however, how microgravity impacts those cellular interactions between mutualistic microbes and their hosts. Here, we used the symbiosis between the host squid Euprymna scolopes and its luminescent bacterium Vibrio fischeri as a model system. We examined the impact of simulated microgravity on the timeline of bacteria-induced development in the host light organ, the site of the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 61 publications
4
57
0
Order By: Relevance
“…The phagocytic capabilities of circulating neutrophils obtained from these postflight astronauts were decreased, whereas the adhesion to endothelial cells was increased (5,6). Monocytes from the blood also showed altered pro-and antiinflammatory cytokine production, increased TLR4 but decreased CD14 expressions, reduced ability to engulf pathogenic Escherichia coli, and an inability to generate an oxidative burst (4,(7)(8)(9). Altered T cell distribution and cytokine production, decreased T cell activation, proliferation, cytotoxic functions, and decreased NK functions were also observed (4,10,11).…”
mentioning
confidence: 99%
“…The phagocytic capabilities of circulating neutrophils obtained from these postflight astronauts were decreased, whereas the adhesion to endothelial cells was increased (5,6). Monocytes from the blood also showed altered pro-and antiinflammatory cytokine production, increased TLR4 but decreased CD14 expressions, reduced ability to engulf pathogenic Escherichia coli, and an inability to generate an oxidative burst (4,(7)(8)(9). Altered T cell distribution and cytokine production, decreased T cell activation, proliferation, cytotoxic functions, and decreased NK functions were also observed (4,10,11).…”
mentioning
confidence: 99%
“…A previous study implicated that gelanolytic activity via a matrix metalloproteinase (MMP) may contribute to this process (Koropatnick et al, 2014) and other work has shown an increase in MMP expression in the light organs of colonized juveniles (Chun et al, 2008) and in hemocytes from symbiotic compared to antibiotic-treated (cured) adult hosts (Collins et al, 2012a; Schleicher et al, 2014). However, regression of the ciliated appendages may not be entirely dependent upon hemocytes, as squid colonized by V. fischeri in simulated microgravity showed a decrease in hemocyte trafficking but an accelerated restructuring of the ciliated appendages (Foster et al, 2013). …”
Section: Hemocyte Interactions With V Fischerimentioning
confidence: 99%
“…To examine the impact of microgravity on beneficial host-microbe interactions in situ , the symbiosis between the Hawaiian bobtail squid Euprymna scolopes and its bioluminescent partner Vibrio fischeri has emerged as tractable model for space biology research24252627. For almost 30 years, this mutualism has enabled the elucidation of fundamental principles associated with horizontally acquired symbioses and their influence on normal animal development282930.…”
mentioning
confidence: 99%
“…Under modeled microgravity conditions, however, many of these bacteria-induced developmental events are altered2627. For example, the trafficking of the hemocytes into the CEA blood sinus is delayed by 10 h in symbiotic animals, and the number of hemocytes within the sinus never reaches levels observed in gravity controls26.…”
mentioning
confidence: 99%
See 1 more Smart Citation